Influence of hydrofluoric acid treatment on electroless deposition of Au clusters - Milazzo, Rachela G.; Mio, Antonio M.; D’Arrigo, Giuseppe; Smecca, Emanuele; Alberti, Alessandra; Fisichella, Gabriele; Giannazzo, Filippo; Spinella, Corrado; Rimini, Emanuele (Beilstein Journal of Nanotechnology, 2017)
The morphology of gold nanoparticles (AuNPs) deposited on a (100) silicon wafer by simple immersion in a solution containing a metal salt and hydrofluoric acid (HF) is altered by HF treatment both before and after deposition. The gold clusters are characterized by the presence of flat regions and quasispherical particles consistent with the layer-by-layer or island growth modes, respectively. The cleaning procedure, including HF immersion prior to deposition, affects the predominantly occurring gold structures. Flat regions, which are of a few tens of nanometers long, are present after immersion for 10 s. The three-dimensional (3D) clusters are formed after a cleaning procedure of 4 min, which results in a large amount of spherical particles with a diameter of ≈15 nm and in a small percentage of residual square layers of a few nanometers in length. The samples were also treated with HF after the deposition and we found out a general thickening of flat regions, as revealed by TEM and AFM analysis. This result is in contrast to the coalescence observed in similar experiments performed with Ag. It is suggested that the HF dissolves the silicon oxide layer formed on top of the thin flat clusters and promotes the partial atomic rearrangement of the layered gold atoms, driven by a reduction of the surface energy. The X-ray diffraction investigation indicated changes in the crystalline orientation of the flat regions, which partially lose their initially heteroepitaxial relationship with the substrate. A postdeposition HF treatment for almost 70 s has nearly the same effect of long duration, high temperature annealing. The process presented herein could be beneficial to change the spectral response of nanoparticle arrays and to improve the conversion efficiency of hybrid photovoltaic devices.
Keywords: electroless deposition; galvanic deposition; gold nanoparticles; HF acid treatment; HF-propelled motion; hydrogen termination; silicon surfaces